Prevalence of Thrombocytosis, Thrombocytopenia, Lymphocytosis and Lymphocytopenia in Patients with Lower Respiratory Tract Infection and Patients with Urinary Tract Infection - Duygu Mert; Alparslan Merdin (Acta Clinica Croatica, 2020)
There are many reasons for abnormal lymphocyte and platelet counts. In this study, we aimed to assess the prevalence of thrombocytosis, thrombocytopenia, lymphocytosis and lymphocytopenia in patients with lower respiratory tract infection (LRTI) and patients with urinary tract infection (UTI). This retrospective study included 52 LRTI patients and 60 UTI patients. Control group consisted of 70 healthy individuals admitted to the infectiology outpatient unit. No statistically significant relationship was found between the groups of subjects and platelet count. Seven (11.7%) UTI patients and four (7.7%) LRTI patients had lymphocytopenia but there was no statistically significant relationship between the groups of subjects and lymphocyte count. Study results suggested a conclusion that lymphocyte and platelet counts could be within the normal ranges in patients with UTI, as well as in those with LRTI.